Continual Deletion of Spinal Microglia Reforms Astrocyte Scar Favoring Axonal Regeneration - Xia, Longkuo; Qi, Jianhuan; Tang, Mingming; Liu, Jing; Zhang, Da; Zhu, Yanbing; Hu, Baoyang (Frontiers in Pharmacology, 2022)
Astrocyte scar formation after spinal cord injury (SCI) efficiently limits the accurate damage but physically restricts the following axon regeneration. Lately, fine tuning scar formation is becoming a novel strategy to develop SCI treatment, yet how to leverage these opposite effects remains challenging. Here, using an improved drug administration approach, we show that in mouse model of spinal cord injury, continual deletion of microglia, especially upon scar formation, by chemical PLX3397 decreases the amount of microglia-derived Collagen I and reforms the astrocyte scar. The astrocytes become less compacted in the scar, which permits axon regeneration and extension. Although continual microglia deletion does not significantly improve the locomotive performance of the SCI mice, it does ameliorate their weight loss, possibly through improvement of the relevant health condition. We thus identify a novel approach to regulate astrocyte scar for improved axon regeneration, which is indicative for clinical treatment of SCI patients.